Use of library resources and services by science faculty members, University of Ibadan: a case study (2014)
This study investigated the use of library resources by the lecturers in the Faculty of Science, University of Ibadan. Six research questions were formulated to guide the study. The descriptive survey design was adopted in the study. The study population comprised the teaching staff in all the 11 departments in the Faculty of Science, University of Ibadan, Nigeria. The instrument for data collection was a structured questionnaire. The findings of the study revealed that only 15.5% of the respondents visit the library frequently to use library resources. Expectedly the basic reasons for library use by the respondents were for research (70.6%) and teaching (36.6%). The extent of awareness of e-resources that are being provided by the library among the respondents was high (72.8%); however, only JSTOR was the most frequently used e-resources by the respondents (35.9%). It is recommended that the library should organize relevant sensitization programmes to increase the use of library and its resources by the respondents.